Haematococcus pluvialis Accumulated Lipid and Astaxanthin in a Moderate and Sustainable Way by the Self-Protection Mechanism of Salicylic Acid Under Sodium Acetate Stress - Hu, Qunju; Song, Mingjian; Huang, Danqiong; Hu, Zhangli; Wu, Yan; Wang, Chaogang (Frontiers in Plant Science, 2021)
To elucidate the mechanism underlying increased fatty acid and astaxanthin accumulation in Haematococcus pluvialis, transcriptome analysis was performed to gain insights into the multiple defensive systems elicited by salicylic acid combined with sodium acetate (SAHS) stresses with a time course. Totally, 112,886 unigenes and 61,323 nonrepeat genes were identified, and genes involved in carbon metabolism, primary and secondary metabolism, and immune system responses were identified. The results revealed that SA and NaAC provide both energy and precursors to improve cell growth of H. pluvialis, and enhance carbon assimilation, astaxanthin and fatty acids production in this microalga with an effective mechanism. Interestingly, SA was considered to play an important role in lowering transcriptional activity of the fatty acid and astaxanthin biosynthesis genes through self-protection metabolism in H. pluvialis, leading to its adaption to HS stress and finally avoiding massive cell death. Moreover, positive correlations between fifteen key genes involved in astaxanthin and fatty acid biosynthesis pathways were found, revealing cooperative relation between these pathways at transcription level. These results not only enriched our knowledge of astaxanthin accumulation mechanism in H. pluvialis, but also provided a new view on increasing astaxanthin production in H. pluvialis by moderate and sustainable way in the future.